Overexpression of Medicago MtCDFd1_1 Causes Delayed Flowering in Medicago via Repression of MtFTa1 but Not MtCO-Like Genes - Zhang, Lulu; Jiang, Andrew; Thomson, Geoffrey; Kerr-Phillips, Megan; Phan, Chau; Krueger, Thorben; Jaudal, Mauren; Wen, Jiangqi; Mysore, Kirankumar S.; Putterill, Joanna (Frontiers in Plant Science, 2019)
Optimising flowering time is crucial for maximising crop productivity, but gaps remain in knowledge of the mechanisms underpinning temperate legume flowering. Medicago, like winter annual Arabidopsis, accelerates flowering after exposure to extended cold (vernalisation, V) followed by long-day photoperiods (LD). In Arabidopsis photoperiodic flowering is triggered through CO, a photoperiodic switch that directly activates the FT gene encoding a mobile florigen and potent activator of flowering. In Arabidopsis, several CDFs, including AtCDF1, act redundantly to repress CO and thus FT expression, until their removal in LD by a blue-light induced GI-FKF1 complex. Medicago possesses a homolog of FT, MtFTa1, which acts as a strong activator of flowering. However, the regulation of MtFTa1 does not appear to involve a CO-like gene. Nevertheless, work in pea suggests that CDFs may still regulate flowering time in temperate legumes. Here we analyse the function of Medicago MtCDF genes with a focus on MtCDFd1_1 in flowering time and development. MtCDFd1_1 causes strong delays to flowering when overexpressed in Arabidopsis and shows a cyclical diurnal expression in Medicago with peak expression at dawn, consistent with AtCDF genes like AtCDF1. However, MtCDFd1_1 lacks predicted GI or FKF1 binding domains indicating possible differences in its regulation from AtCDF1. In Arabidopsis CDFs act in a redundant manner and the same is likely true of temperate legumes as no flowering-time phenotypes were observed when MtCDFd1_1 or other MtCDFs were knocked out in Medicago Tnt1 lines. Nevertheless, overexpression of MtCDFd1_1 in Medicago plants resulted in late flowering relative to wild type in inductive VLD conditions, but not in vernalised short days (VSD), rendering them day neutral. Expression of MtCO-like genes was not affected in the transgenic lines, but LD-induced genes MtFTa1, MtFTb1, MtFTb2 and MtSOC1a showed reduced expression. Plants carrying both the Mtfta1 mutation and 35S:MtCDFd1_1 flowered no later than Mtfta1 plants. This indicates that 35S:MtCDFd1_1 likely influences flowering in VLD via repressive effects on MtFTa1 expression. Overall, our study implicates MtCDF genes in photoperiodic regulation in Medicago by working redundantly to repress FT-like genes, particularly MtFTa1, but in a CO-independent manner indicating differences from the Arabidopsis model.